DOES NET FOREIGN ASSETS AND EXCHANGE RATE HAVE THRESHOLD EFFECT ON BALANCE OF TRADE IN NIGERIA? - OSINUSI , KUNLE. B; SOKUNBI, ADEPEJU REBECCA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study adopted an ex post facto research design in the analysis of NFA, REER and TB datasets sourced from secondary sources from 1982 to 2023. The technique used to check for the extent to which net foreign assets, real effective exchange rate and interest rate affect trade balance and GDP growth rate is threshold analysis. The result revealed that a linear threshold effect between TB and GDP growth rate when REER is either greater or less than #207.5, NFA is either greater or less than 9492.4, and RIR is either greater or less than 4.59 per cent in Nigeria that is what occurs at the lower regime also occur at the higher regime. Between NFA and GDP growth rate, there is also a negative linear threshold effect when RIR is either greater or less than 4.59 per cent and non-linear threshold effect exist between NFA and GDP growth rate when REER is either greater or less than #207.5, same as with REER and GDP growth rate. Therefore, it is recommended that policymakers should adopt differential policy approaches to address economic challenges. Policies tailored to specific economic regimes can help mitigate structural breaks and promote stability in key macroeconomic indicators. Finally, policymakers should prioritize strategies to optimize NFA management. This may involve diversifying foreign asset portfolios, attracting long-term foreign investments, and enhancing capital inflows to support economic growth and mitigate structural breaks in the relationship between NFA and GDP growth